A comparative study on growth and degradation behavior of C. pyrenoidosa on synthetic phenol and phenolic wastewater of a coal gasification plant. Issue 3 (June 2019) - S., Dayana Priyadharshini; A.K., Bakthavatsalam
Graphical abstract: Highlights: C. pyrenoidosa was cultivated in untreated coal gasification effluent. Degradation kinetics of phenol and phenolic effluent is compared. C. pyrenoidosa degrades average of 97.4% of phenol concentrations up to 0.8 g/L. C. pyrenoidosa can grow in coal gasification effluent under ambient conditions. Abstract: Phenol and its derivatives are highly hazardous chemicals profoundly dangerous even at low levels. Hence the management of phenol polluted wastewater represents major environmental challenges. This study investigates the growth and the phenol utilization behavior of microalga DEE 01 isolated from coal gasification effluent treatment plant and identified as Chlorella pyrenoidosa based on 18SrRNA sequence analysis (KX686118). The average % reduction of phenol concentration of the four samples (0.2, 0.4, 0.6 and 0.8 g/L) by C. pyrenoidosa is 97.4% under local ambient conditions at pH-8. It could also degrade phenol in the coal gasification effluent. Haldane inhibitory growth kinetics was used to fit the experimental data and the kinetic parameters obtained were: μ max  = 0.7123 day −1, K s  = 0.1899 gL −1 ; K i  = 0.6898 gL −1 with R 2  = 0.9916. In addition to the phenol reduction C. pyrenoidosa was found to reduce the metal ions present in the effluent. The kinetic study of C. pyrenoidosa is observed to possess maximum specific growth and degradation rate, tolerance to toxicity ( K i ) and high phenol affinity ( K s ).